2021
DOI: 10.1007/s13199-021-00823-y
|View full text |Cite
|
Sign up to set email alerts
|

Photoprotection and high-light acclimation in semi-arid grassland lichens – a cooperation between algal and fungal partners

Abstract: In lichens, each symbiotic partner cooperates for the survival of the symbiotic association. The protection of the susceptible photosynthetic apparatus is essential for both participants. The mycobiont and photobiont contribute to the protection against the damaging effect of excess light by various mechanisms. The present study investigated the effect of seasonality and microhabitat exposure on photoprotection and photoacclimation in the photo- and the mycobiont of six lichen species with different thallus mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 89 publications
0
9
0
Order By: Relevance
“…It can be concluded that the algae were more sensitive to the seasonally changing environment than the acetone treatment. The treatment mostly affected the mycobiont partner and the algae did not elevate their photoprotective role (φNO and φNPQ did not differ in the control and treated thalli), as Veres et al ( 2022 ) pointed out in Cladonia furcata . Probably the initial amount of UV-protectant lichen metabolite originated from a high level of constitutive photoprotection (Asplund et al 2009 ), and the system was over-secured.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…It can be concluded that the algae were more sensitive to the seasonally changing environment than the acetone treatment. The treatment mostly affected the mycobiont partner and the algae did not elevate their photoprotective role (φNO and φNPQ did not differ in the control and treated thalli), as Veres et al ( 2022 ) pointed out in Cladonia furcata . Probably the initial amount of UV-protectant lichen metabolite originated from a high level of constitutive photoprotection (Asplund et al 2009 ), and the system was over-secured.…”
Section: Discussionmentioning
confidence: 60%
“…Therefore, the thalli of Cladonia foliacea can survive for years after acetone treatment. Veres et al ( 2022 ) pointed out that C. foliacea contained approximately four times more cortical pigment (usnic acid) compared to, for example, C. furcata or C. magyarica containing atranorin in their cortex derived from the same microhabitat collected at the same time. Probably the usnic acid can significantly contribute to the survival of C. foliacea in habitats with extreme irradiation and drought, helping the thalli against photodamage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As part of our investigation, we not only measured the photosynthetic activity of the lichens in their nonsoaked state, but also irrigated them for a period of two hours, since the importance of hydrating the samples under investigation before measuring their physiological parameters has already been shown in the previous study (Węgrzyn et al 2021b). Exposure to the sunlight of the dry lichen thallus can cause the accumulation of severe damage in PS II, and water is the endogenous factor for the regeneration of the damaged apparatus (Veres et al 2022a). In the study, the hydrated form of C. mitis showed signi cantly higher levels of photosynthetic activity than the non-soaked thallus, which is a natural process that occurs in lichens (Grimm et al 2021;Wegrzyn et al 2021).…”
Section: Photosynthetic Activitymentioning
confidence: 99%